2D semi-analytical solutions for single layer piezoelectric laminate subjected to electro-mechanical loading. (February 2015) - Pendhari, Sandeep S.; Sawarkar, Sameer; Desai, Yogesh M.
Abstract: Analysis of a piezoelectric laminate under plane strain condition of elasticity (cylindrical bending) has been performed with mixed semi-analytical model developed by Kant et al. (2007). The in-plane displacement, transverse displacement, transverse normal and shear stresses, electric potential and transverse electric displacement have been considered as fundamental dependent variables. The mathematical model consists of defining a two-point boundary value problem (BVP) governed by a set of coupled first order ordinary differential equations (ODEs). The accuracy and efficiency of the proposed model are assessed by comparing the numerical results from the present investigation with available elasticity solutions.